2023
DOI: 10.1088/1674-1056/ac8f3d
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting amplitude of the stored optical solitons by inter-dot tunneling coupling in triple quantum dot molecules

Abstract: We study the propagation properties of a probe field in an aligned asymmetric triple quantum dot molecule with both sides inter-dot tunneling coupling effect. It is shown that the probe field can form optical soliton due to the destructive quantum interference induced by the quantum inter-dot tunneling coupling effect. Interestingly, these optical solitons can be stored and retrieved by adjusting single or double inter-dot tunneling coupling effect, different from that light memory in the ultra-cold atom syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
2
0
1
Order By: Relevance
“…These phenomena can be effectively harnessed for various practical applications. [35][36][37][38][39][40][41][42][43] We concentrate on achieving optimal and robust population transfer in an asymmetric double quantum-dot molecule (ADQDM). [44][45][46][47][48] The present system consists of two SQDs with distinct band structures connected through tunneling.…”
Section: Introductionmentioning
confidence: 99%
“…These phenomena can be effectively harnessed for various practical applications. [35][36][37][38][39][40][41][42][43] We concentrate on achieving optimal and robust population transfer in an asymmetric double quantum-dot molecule (ADQDM). [44][45][46][47][48] The present system consists of two SQDs with distinct band structures connected through tunneling.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of nonlinear optics, researchers have shifted their attention to studying the propagation characteristics of individual optical solitons while also studying the transmission of multiple optical solitons in optical fibers and fiber lasers. [1][2][3][4][5][6][7] Research has shown that when there are two or more optical solitons in a fiber, they will interact with each other, attracting or repelling each other like particles. [8][9][10] Under certain initial conditions, complex interactions between optical solitons can lead to a series of interesting nonlinear phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Michael等 [43] 发现点间TIT不仅可以抑制介质对 光的吸收, 而且还可以调节光通过系统的传播速 度. 让一束探测光通过量子点EIT介质去传播 [44,45] , 发现体系所形成的光孤子能够存储起来. 佘彦超 等 [46] 发现通过调节TIT强度能使体系产生双透明 窗口, 且系统所产生的时间孤子是亮孤子还是暗孤 子完全由控制光强的强度来确定.…”
unclassified